PROBLEMATIKA PEMBELAJARAN DARING ANAK SEKOLAH DASAR DISDIUFADLUNNAFISBANGSRI - Yuyun Fatmawati (Universitas Islam Nahdlatul Ulama Jepara, 2021)
The purpose of this study was to analyze the problem of online learning during the Covid-19pandemic and solutions to solve them at SDIU Fadlun Nafis Bangsri. This type of research isliterature study or library research using secondary data sources collected through textbook, e-books,perodical,statutoryregulations,websites,andothersourcesrelevanttotheresearchproblem. In thus research, it shows that the implementation of online learning at SDIU Fadlun NafisduringtheCovid-19pandemichasvariousproblemsexperiencedbyteachers,student,andparents. Problems from students and parents such as lack of student responsibility for onlinelearning, weak levels of student understanding, delays in submitting assignments due to busyparentsworking toforget that theyhavent been done, weakening student discipline, enthusiasmfor playing games is stronger than learning online. The obstacles from the teacher themselves areinaccurate assessment, the length of time making learning video content interesting for students,creativity in editing videos, and the inadequate capacity of cellphones for editing videos. In general,the solution to these problems can be done by collaborating and establishing communicationbetween teachers, students and parents in understanding and providing feedback on the learningprovidedby theteacher.Keyword:Problemtics,OnlineLearning